They are only different: discursive production of contemporary masculinities in the book Raising Boys - Juliana Ribeiro de Vargas; Rodrigo Saballa de Carvalho (Universidade Federal de Santa Maria, 2013)
From Gender Studies, in its post-structural model, and from the cooperation of Cultural Studies in Education, this article aims to problematize the discursive production of masculinities in the book Raising Boys, by Steve Bidduph. This work has associated determined behaviors as typically belonging to boys of different ages, and it has presented a regulation of attitudes they should have in relation to boys to mothers, fathers and teachers, in order to favor these children's development, guiding them, thus, to determined ways of living/experiencing sexuality. From the mentioned contributions, there was an attempt to problematize this book as a cultural artifact, which develops a cultural pedagogy that, through the naturalization of some characteristics presented by boys, ends up regulating the constitution of male sexuality, and teaching adults how to promote it.